(untitled) (Nigerian Journal of Pharmaceutical Research, 2020)
Background: Concurrent use of herbal and orthodox medicines can result in herb-drug interaction, which could remain unidentified due to the limited knowledge of health care providers on herbal medicines effects and safety. Objectives: This study aimed to assess the knowledge of medical and pharmacy students of the University of Lagos on herbal medicines and herb-drug interactions. Method: The study was a cross-sectional survey of final year pharmacy and medical undergraduate students (422) of the University of Lagos. Data was collected using a validated, previously developed, and standardized self-administered questionnaire. Descriptive statistics was used to evaluate the students’ demographics, knowledge of herbal medicines and herb-drug interactions, types and uses of herbal medicines, while inferential statistics was employed to assess the association between the students’ demographics and their knowledge of herb-drug interactions. Statistical significance was set at P<0.05. Results: The response rate was 97%. The students (98.0%) knew that herbs can be used as medicines; common uses of herbal medicines reported by the students include malaria (11.4%), pain (24.6%), and fever (36.2%). There was no association between the students’ demographics and their knowledge about herbal medicine. Age was significantly associated with knowledge of herb-drug interaction (P<0.05). The students (96.8%) knew that herbs can interact with conventional drugs when administered concurrently. The sources of the students’ knowledge about herbal medicine and herb-drug interaction include lectures (52.2%), literature (14%) and personal experience (13.9%). Conclusion: The students had good knowledge of herbal medicines; however, the subject of herbal medicines and their effects should be given more attention in the medical and pharmacy program curriculum, in order to enhance the students’ knowledge base of herbal medicines and interactions, and equip the future physicians and pharmacists adequately for better patient care.